Well it has to be 3*2 = 6 square feet. Note: first convert 36 inches to 3 feet and 24 inches to 2 feet.
Answer: h(-4)
Step-by-step explanation:
If h(x) something is equal to 4 then set the equation equal 4 and solve for t.
4t +20 = 4
-20 -20
4t = -16
t = -4
So h(-4) = 4
Answer:
x = -4
Step-by-step explanation:
3x + 5 = x - 3
Subtract x from each side
3x+5-x = x-3-x
2x+5 = -3
Subtract 5 from each side
2x+5-5 = -3-5
2x = -8
Divide each side by 2
2x/2 = -8/2
x = -4
Step-by-step explanation:
f(x)=2x²+3x+9
g(x) = - 3x + 10
In order to find (f⋅g)(1) first find (f⋅g)(x)
To find (f⋅g)(x) substitute g(x) into f(x) , that's for every x in f (x) replace it by g (x)
We have
(f⋅g)(x) = 2( - 3x + 10)² + 3(- 3x + 10) + 9
Expand
(f⋅g)(x) = 2( 9x² - 60x + 100) - 9x + 30 + 9
= 18x² - 120x + 200 - 9x + 30 + 9
Group like terms
(f⋅g)(x) = 18x² - 120x - 9x + 200 + 30 + 9
(f⋅g)(x) = 18x² - 129x + 239
To find (f⋅g)(1) substitute 1 into (f⋅g)(x)
That's
(f⋅g)(1) = 18(1)² - 129(1) + 239
= 18 - 129 + 239
We have the final answer as
<h3>(f⋅g)(1) = 128</h3>
Hope this helps you